The efficacy of transcranial direct current stimulation in the treatment of anorexia nervosa: a randomized double-blind clinical trial - Rząd, Zuzanna; Rog, Joanna; Kajka, Natalia; Szewczyk, Paweł; Krukow, Paweł; Karakuła-Juchnowicz, Hanna (Frontiers in Psychiatry, 2024)
Background: Anorexia nervosa (AN) is a life-threatening disease with a low effectiveness of treatment. The high relapse and mortality rate indicate new treatment approaches are needed. Here, we represent the protocol for randomized clinical trial (RCT) of transcranial direct current stimulation (tDCS) efficiency in the AN treatment. The main purpose of the 3-week RCT is to determine the effect of tDCS on the mental state and advances in nutritional rehabilitation in patients with AN. Methods: 50 female inpatients (13-25 years old, body mass index (BMI) 17.5 kg/m2 or less) will be randomly allocated into groups: active (n=25) and sham (n=25) tDCS. Thirty 25-minute tDCS sessions (applied current at 2mA) will be given to DLPFC (F3 anode/ F4 cathode) twice a day for 3 weeks on working days parallel to treatment as usual. The primary outcome measures include changes in symptoms related to eating disorders, as assessed by the Eating Attitudes Test (EAT-26), following tDCS sessions over a 3-week trial period. The secondary outcome measures include changes in: brain bioelectric activity, anthropometric measurements, mood, nutritional status, neurocognition, psychological symptoms, selected biological markers related to stress, food intake, inflammation and neurotrophins. Discussion: This paper describes the evaluation of a 3-week tDCS-based intervention for AN patients. The study design was developed by a multidisciplinary research team to assess the treatment effect, taking into account various types of variables. This approach could help in better understanding the potential therapeutic tDCS strategy in AN.